2018
DOI: 10.3390/ijms19092608
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iron Overload and Oxidative Damage on the Musculoskeletal System in the Space Environment: Data from Spaceflights and Ground-Based Simulation Models

Abstract: The space environment chiefly includes microgravity and radiation, which seriously threatens the health of astronauts. Bone loss and muscle atrophy are the two most significant changes in mammals after long-term residency in space. In this review, we summarized current understanding of the effects of microgravity and radiation on the musculoskeletal system and discussed the corresponding mechanisms that are related to iron overload and oxidative damage. Furthermore, we enumerated some countermeasures that have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 130 publications
2
24
0
2
Order By: Relevance
“…The biological role of diverse nutritional, nutraceutical, and aromatic iotas is worthy of being studied, considering that beneficial components can be incorporated directly into new chemotypes [ 2 , 80 , 81 ]. For instance, space travelers will need extra calcium and vitamin D for bone weakening, the proper amount of proteins to counteract sarcopenia, low iron to avoid overload, and low-sulfur protein intake for acid-base balancing [ 54 , 82 , 83 , 84 , 85 ]. Extra flavor molecules to increase food enjoyment may be necessary because astronauts may experience a dulling of the olfaction that is known to reduce food intake [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological role of diverse nutritional, nutraceutical, and aromatic iotas is worthy of being studied, considering that beneficial components can be incorporated directly into new chemotypes [ 2 , 80 , 81 ]. For instance, space travelers will need extra calcium and vitamin D for bone weakening, the proper amount of proteins to counteract sarcopenia, low iron to avoid overload, and low-sulfur protein intake for acid-base balancing [ 54 , 82 , 83 , 84 , 85 ]. Extra flavor molecules to increase food enjoyment may be necessary because astronauts may experience a dulling of the olfaction that is known to reduce food intake [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Summary II. A total of 33 references ([ 7 , 10 , 20 , 21 , 22 , 23 , 27 , 45 , 46 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 59 , 60 , 61 , 62 , 63 , 64 , 66 , 67 , 68 , 73 , 76 , 77 , 79 , 82 , 83 , 84 , 85 ]) were used to scope the following nutritional commonalities between post-operative (hospital-based) vs. space station (planetary) issues. The use of single-serving prepackaged meals; the need to establish demand-driven systems that crosstalk and reduce food waste; the importance of guaranteeing food safety and human engagement throughout the process; the need to support the musculoskeletal health; the interest in some nutrients (i.e., proteins, calcium, iron, vitamin D); the need for boosting food flavors to increase appetite, palatability, hedonic appreciation, and food intake.…”
Section: Resultsmentioning
confidence: 99%
“…We summarize the reactions of both the innate and the adaptive immune cells to different types of MFs in Table 1. Generally, upon exposure to a very low-frequency AMF (50-75 Hz, 0.8-7 mT), the innate immune cells get more activated and initiate the inflammatory responses in mice and rats (9,(16)(17)(18)(19)(20)(21). Natural killer cells (NK cells) are found to be more cytotoxic under 0.4 T SMF Abbreviations: AMF, alternating magnetic fields; DC, dendritic cell; EMF, electromagnetic field; FTH, heavy chain H-ferritin; FPN1, ferroportin-1; GPX4, glutathione peroxidase; HGMF, high-gradient magnetic field; HO-1, heme oxygenase-1; MDSC, myeloid-derived suppressor cell; MF, magnetic field; MRI, magnetic resonance imaging; NK cell, natural killer cell; NP, nanoparticle; OC, osteoclast; ROS, reactive oxygen species; SMF, static magnetic field; TCR, T-cell receptor; TfR1, transferrin receptor-1.…”
Section: Immune Reactions Under Various Types Of Mfsmentioning
confidence: 99%
“…When stimulated by mechanical strain (Wang et al, 2019), osteocytes can regulate osteoblast proliferation and differentiation by releasing signaling molecules, such as nitric oxide, prostaglandin E2, and adenosine triphosphate (Bakker et al, 2001;Genetos et al, 2005). Studies have shown that bed-ridden patients and astronauts develop osteoporosis due to reduced mechanical bone stimulation, but the mechanism of this phenomenon remains unclear (Norvell et al, 2004;Sibonga, 2013;Yang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%